A new classification of peri‐implant bone morphology: a radiographic study of patients with lower implant‐supported mandibular overdentures. Issue 8 (30th May 2013) - Zhang, Lei; Geraets, Wil; Zhou, Yongsheng; Wu, Wuqing; Wismeijer, Daniel
Abstract Objective This study aimed to classify peri‐implant bone defects (PIBDs) on the basis of their radiographic appearance in a cohort of patients with lower implant‐supported overdentures. Materials and methods Eighty‐three patients with lower implant‐supported overdentures were recruited to participate in the study, which was approved by the ethics committee of Ignatius Teaching Hospital. Details about the patients' smoking habits were recorded. The participants had a total of 224 implants involving 3214 implant sites. The mean observation time of the subjects was 10.7 years. Panoramic radiographs of all sites were evaluated in duplicate (first evaluation [t1], second evaluation [t2]) during 2 weeks by one experienced observer. PIBDs were classified into the following types: saucer‐shaped, wedge‐shaped, flat, undercut, and slit‐like bone defects. Intra‐examiner agreement was tested using crosstabs and Cohen's kappa coefficient. The association of PIBD type with gender, time after implant placement, smoking, and treatment strategy was investigated using multivariate test of independence on the basis of spatial signs. Results Intra‐observer reliability was moderate (κ = 0.51). Saucer‐shaped defects were the most frequent (42.8% [t1] and 44.6% [t2]), followed by wedge‐shaped (26.0% [t1] and 27.4% [t2]), flat (10.7% [t2] and 17.7% [t1]), undercut (8.8% [t1] and 11.9% [t2]), and finally slit‐like defects (4.7% [t1] and 5.4% [t2]). Peri‐implant bone defects morphology was significantly associated with gender, smoking, and treatment strategy. Conclusion The morphology of PIBDs can be classified into five meaningful classes, as opposed to the two described in the literature.